Virtual reality intervention to improve apathy in residential aged care: protocol for a multisite non-randomised controlled trial. Issue 2 (1st February 2021) - Saredakis, Dimitrios; Keage, Hannah A D; Corlis, Megan; Loetscher, Tobias
Abstract : Introduction: Apathy is a prevalent neuropsychiatric symptom for older adults residing in aged care. Left untreated, apathy has been associated with accelerated cognitive decline and increased risk of mortality. Reminiscence therapy is commonly used in aged care and has demonstrated to reduce apathy. Traditional methods of reminiscence use physical objects and more recently technology including tablets and laptop computers have demonstrated potential. Virtual reality (VR) has successfully been used to treat psychological disorders; however, there is little evidence on using VR for behavioural symptoms such as apathy in older adults. Using VR to deliver reminiscence therapy provides an immersive experience, and readily available applications provide access to a large range of content allowing easier delivery of therapy over traditional forms of therapy. This study aims to identify changes in apathy after a reminiscence therapy intervention using head-mounted displays (HMDs). Methods and analysis: Participants will be allocated to one of three groups; reminiscence therapy using VR; an active control using a laptop computer or physical items and a passive control. A total of 45 participants will be recruited from residential aged care (15 in each group). The three groups will be compared at baseline and follow-up. The primary outcome is apathy, and secondary outcomes include cognition and depression. Side effects from using HMDs will also be examined in the VR group. Primary and secondary outcomes at baseline and follow-up will be analysed using linear mixed modelling. Ethics and dissemination: Ethics approval was obtained from the University of South Australia Human Research Ethics Committee. The results from this study will be disseminated through manuscript publications and national/international conferences. Trial registration number: ACTRN12619001510134.